2008
DOI: 10.1177/0883073808318052
|View full text |Cite
|
Sign up to set email alerts
|

Possible Pathogenic Link Between Migraine and Urotensin-II

Abstract: Our aim was to determine the levels of human urotensin-II (hU-II) in the plasma of migraine patients and controls, to ascertain if there were a difference in the pathogenesis of migraine. A total of 27 patients who suffer from migraines and 27 controls were included in the study. Venous blood samples were drawn twice both from migraine patients and controls to measure hU-II plasma levels. The average levels of hU-II during migraine episode, between episodes, and controls were found to be 0.483, 0.493, and 0.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
3
0
2
Order By: Relevance
“…The roles that plasma UTS2R levels play during headache attacks and headache-free periods in migraine patients have also been reported in clinical studies. 10 , 11 , 31 Bicak et al 31 observed lower levels of UTS2R in pediatric patients during migraine episodes compared to healthy controls, which is in agreement with the present findings. However, the present results contradict those of Geyik et al, 10 who showed that UTS2R levels were higher in patients with migraine than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…The roles that plasma UTS2R levels play during headache attacks and headache-free periods in migraine patients have also been reported in clinical studies. 10 , 11 , 31 Bicak et al 31 observed lower levels of UTS2R in pediatric patients during migraine episodes compared to healthy controls, which is in agreement with the present findings. However, the present results contradict those of Geyik et al, 10 who showed that UTS2R levels were higher in patients with migraine than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…There are few studies indicating that the U-II plasma levels do not differ between women and men [22,23]. However, a study has shown it to be lower in women [24].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have indicated that there are no significant differences in plasma UII levels between males and females (10,24,65,70,129), whereas another study reported lower plasma levels of UII in women (89). The possibility of age or gender differences in UII expression, however, has yet to be rigorously explored.…”
Section: Circulating Uii In the Plasmamentioning
confidence: 99%